(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2019)
Biological activity of the carotenoids which are produced fromchemically-mutaed local isolate of Rhodotorula mucilaginosawas studied. The results showed variation of inhibition activity of caritenoids against different types of pathogenic bacteria include, Staph aureus, E. coli, B. subtilis and Salmo. typh., the number declined from 2×107cell/ml to 2×104, 5×104, 2×105, 9×105 cell/ml respectively after 24hour. The produced carotenoids from alocal mutant Rhodotorula mucilaginosa revealed an antioxidant activity as free radical removal of 85.6%. Carotinoides revealed a highest stability in petroleum ether solvent for 30 days at room temperature. It found that the pigment was more stability in sesame oil compared with sun flower and coconut oil. The pigment revealed a high stability in the dark for 30 days compared with its stability in the light either were stored in petroleum ether or sesame oil with note the pigment high stability at refrigerator temperature (4ºC) and the good stability at room temperature (25ºC).